Organic matter degradation and bacterial communities in surface sediment influenced by Procambarus clarkia - Hou, Yiran; Jia, Rui; Ji, Peng; Li, Bing; Zhu, Jian (Frontiers in Microbiology, 2022)
To alleviate excessive organic matter (OM) accumulation in sediments and reduce the risk of endogenous water pollution and eutrophication in aquaculture ponds, an 84-day experiment investigated the effect of the red swamp crayfish Procambarus clarkii on the OM degradation and bacterial communities in sediments. The experiment established two groups, P. clarkia treatment and control (represented as PG and CG, respectively), with three replicates for each group. At the end of experiment, the total, light fraction, and heavy fraction organic matter concentrations in the sediment of the PG group were significantly lower than those of the CG group. Significantly higher oxidation-reduction potential (ORP) and more extensively degraded OM, indicated by fatty acids, were observed in the PG group. Compared to the CG group, the average OM removal efficiency induced by crayfish in the PG group was 15.24%. Using 16S ribosomal RNA (rRNA) high-throughput sequencing, we investigated the differences in benthic bacterial communities between the PG and CG groups. Linear discriminant analysis (LDA) effect size (LEfSe) analysis revealed that Nitrospirae, Nitrospira, Alphaproteobacteria, OLB14, Nitrospirales, Rhodobacterales, Rhizobiales, Micrococcales, Nitrospiraceae, Rhodobacteraceae, Nitrospira, Rhodobacter, Thermomonas, and Denitratisoma were significantly enriched in the PG group. Four significantly different functional groups related to OM degradation were determined between the PG and CG groups according to the functional annotation of procaryotic taxa (FAPROTAX) analysis. These four functional groups, aerobic chemoheterotrophy, manganese oxidation, dark iron oxidation, and dark sulfide oxidation, showed significantly higher relative abundances in the PG group. Overall, P. clarkia effectively increased the ORP values of sediments to provide favorable conditions for OM degradation and changed the composition and function of bacterial communities to improve bacterial abilities for OM decomposition, thereby promoting OM degradation in the sediment.